PENGARUH PENGETAHUAN DAN SIKAP GURU DAN SISWA TENTANG ROKOK DAN KEBIJAKAN KAWASAN TANPA ROKOK TERHADAP PARTISIPASI DALAM PENERAPAN KAWASAN TANPA ROKOK DI SMP NEGERI 1 KOTA MEDAN TAHUN 2012 - Imelda christina (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2012)
SMP Negeri 1 Medan State is one of an international school. SMP Negeri 1 is already implementing a free-smoke area in 2009. This policy has not been effective, because it is still seen in some rooms there are teachers who smoke. SMP Negeri 1 not set clear limits on the free-smoke area. This school has a place in the specialize to smoke, but the location of the canteen, cooperative and Teacher’s room, still seen who teachers smoke. This research is explanatory research survey that aims to explains the influence of knowledge and attitudes about cigarette smoking and of free-smoke area policy against participation in the implementation of free smoke areas in SMP Negeri 1 Medan in 2012.The study population was all students and teachers of SMP Negeri 1 Medan, amounting to 884 people and total sampling is 90 people were taken by purposive sampling. Primary data was collected through interviews, and data analysis with logistic regression test. The results showed that attitudes about smoking and free-smoke area policy has an influence on participation in the implementation of free-smoke areas (p=0,009). It is expected that school leaders to implement of free-smoke area effectively and to all those in the school participated in creating free smoke area in SMP Negeri 1 Medan. Keywords: Free-smoke area, participation of free-smoke area